Characteristics of Pigeon Pea (Cajanus Cajan) Isoflavones Daidzein in Blood on Ovarian And Mammary Tissue Structure Rat Female - Primiani, Cicilia Novi; Pujiati, Pujiati (Universitas Sebelas Maret, 2016)
The use of synthetic hormone preparations, one of the hormones estrogen widely used by people in the care and treatment of diseases as hormone replacement therapy. Pigeon pea (Cajanus cajan) as local Leguminoceae plant has not been used optimally as estrogenic plants . The purpose of this study was to identify preclinical to analyze the Cajanus cajan in the blood profile and potential of the reproductive organs as phytoestrogens. The research method using 24 Sprague -Dawley female rats 6-7 months , grouped 3 treatment. The control group , the treatment group pigeon pea solution of 1 : 1 and group treatment solution pigeon pea 1 : 3. Blood sampling on the 8th, 16th hour and the 24th hour (fractions I, fractions II and fractions III ) for the analysis of isoflavones daidzein HPLC method . Treatment pigeon pea solution made up to 36 days. Surgery and organ harvesting ovarian and mammary continued hematoxylin eosin staining . The results showed levels of isoflavones daidzein maximum in treatment 1 : 1, fractions I, II , and III respectively 92773.474 pg / l ; 96766.278 pg / l ; 72033.062 pg / l. Tissue structure experiencing development of ovarian follicles and germinal proliferation, proliferation of mammary tissue experiencing the lobules and ducts interlobularis development. Conclusion of the study is the pigeon pea daidzein levels in the blood increased in the 24th hour and potential as a natural estrogen.Key Word : daidzein, phytoestrogens, ovarian, mammary